Particle clauses - Smolej, Mojca (Slovenski jezik, 2015)
The role of modification is often fulfilled by particle clauses, which enter into coordinate or subordinate relations with the preceding or following clause structures only at the formal, syntactic level, leaving the semantic level relation unrealised. An indispensable prerequisite for obtaining a grasp of the syntactic and semantic roles of particle clauses is to approach them from the construction perspective, as the construction method involves in its analysis both meaning and form, that is, structure. At the formal level, the two clauses of "Če se na glavo postaviš, ti ne dam" (SSKJ2) enter into a subordinate syntactic relationship, which, however, remains unfulfilled at the semantic level: a case of the so-called pseudo-hypotaxis. The construction method, taking into account both form and content, shows that the clause "če se na glavo postaviš" as a whole reinforces the certainty (epistemic modality), and is thus functionally akin to the word class represented by particles or, more precisely, to the modal group of particles. Moreover, the construction method shows that the reinforcement of certainty is due not only to the use of the lexeme če (as the dictionary explanation seems to suggest) but to every element, lexical or grammatical, which forms part of the structure in question.
Keywords: členek; členkovni stavek; semantics; semantika; skladnja; Slovene; slovenščina; syntax